ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Azis, Safira Nurmalika; Rahardjo, Shiddiq Nur (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2020)
This study aims to examine whether financial ratios have an influence on financial distress. The dependent variable in this study is financial distress which is measured using a dummy variable. The independent variables in this study are CAR, NPL, ROA, ROE and capital structure. In addition, this study also uses the Altman model to determine the level of bankruptcy in banks This study also uses dummy variables to find out which banks are healthy and unhealthy. Hypothesis testing of this study was carried out using logistic regression analysis. This study provides statistical results that show that the CAR has a negative and significant effect on financial distress, ROA has a negative and significant effect on financial distress and the capital structure has a positive and significant effect on financial distress. Whereas NPL and ROE do not have an influence on financial distress.